A numerical typhoon track prediction model and its application on the real-time operation - WANG, SHIWEN; CHENG, DEHUI; LI, JIANJUN; MA, SHUHONG (MAUSAM, 1997)
ABSTRACT. Recently a nested numerical model for typhoon track prediction (MTP) with a higher horizontal resolution and a complex physical package has been developed by the National Meteorological Center (NMC, Beijing). For its improvement of initialization, a modified typhoon bogus scheme (Iwasaki 1987) also has been applied. The design of the M1TP had been determined by the end of 1992 and the forecast capability of this model was tested firstly with a series of experiments for the selected typhoon cases in 1993 (Wang and Li 1994). After it was examined in real-time forecast in the next year, further improvements were made in 1995 including a higher horizontal resolution increased from about 100 to 50 km, a package of complex physics instead of the simple one and a scheme for removal of analyzed vortex. With the improved forecast capability, the MTP run in quasi-operation from the date of 1 June 1995. Its products were also used by the forecasters during the past two years and the results were very encouraging.